2017
DOI: 10.1002/pen.24692
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recycling on the structure and properties of carbon nanotube‐filled polycarbonate

Abstract: Sustainable manufacturing processes are becoming more important in industrial practice. A critical part of the manufacturing process is understanding the recycling behavior of nanocomposite materials, particularly as more recycled plastic nanocomposites are entering the market for a variety of different applications. A common method to recycle thermoplastic composites is by melting and remolding, which often leads to decreased mechanical properties. This work was conducted to investigate the effect of nanofill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Actually, mechanophysical properties of polymer-filler nanocomposites are strongly dependent on the polymer matrix, as far as their resistance to recycling is concerned. Zhang et al [35] studied carbon nanotube (CNT) filled polycarbonate (PC) composites and compared their behavior, after several cycles of injection molding recycling, with neat PC which has undergone the same treatment. The authors found that, by increasing the number of cycles, the filled polymers were more sensitive to the higher shear stress involved during the injection processing.…”
Section: Mechanical Testsmentioning
confidence: 99%
“…Actually, mechanophysical properties of polymer-filler nanocomposites are strongly dependent on the polymer matrix, as far as their resistance to recycling is concerned. Zhang et al [35] studied carbon nanotube (CNT) filled polycarbonate (PC) composites and compared their behavior, after several cycles of injection molding recycling, with neat PC which has undergone the same treatment. The authors found that, by increasing the number of cycles, the filled polymers were more sensitive to the higher shear stress involved during the injection processing.…”
Section: Mechanical Testsmentioning
confidence: 99%
“…The technical data from previous works have been taken into consideration in order to implement Solidworks. Hence, the materials that are candidate to replace the metallic surfaces of ordinary sandwich panels due to their superiority as observed in the literatures are recycled polypropylene (PP)/3% carbon nanotubes (CNT) composite (Liu and Gao, 2011) symbolized as PPC, recycled HDPE/4% nano graphene composite (Reddy, 2006) termed (HDPEC), and recycled polycarbonate (PC)/3% CNT composite (Zhang, et al, 2017) abbreviated as PCC. Accordingly, yield strength, ultimate strength, and modulus of elasticity were directly extracted from aforementioned works.…”
Section: A Technical Data Of the Materialsmentioning
confidence: 99%
“…In general, recycled materials show a loss of mechanical properties due to degradation processes occurring during processing, life cycle and mechanical recycling [ 20 , 21 ]. The degree of degradation of recycled plastic can vary from plastic to plastic, depending on the degradation processes associated with the polymer matrix, such as thermos-oxidative and shear-induced chain scission, chain branching or cross-linking [ 25 , 26 , 27 , 28 , 29 ], which in turn affect the processability and lower the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The PP/CNT nanocomposites showed an increase in toughness with recycling due to the changes in the crystallization behavior, while the presence of CNTs improved the recycling resistance. Zhang et al [ 26 ] analyzed the effect of the recycling process on the PC filled with 3 wt.% of CNTs up to twenty cycles. The research showed no significant changes in the chemical structure of the recycled PC/CNT nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation